Periodontitis-associated metabolite isoleucine impairs intestinal barrier function and exacerbates intestinal inflammatory response by NF-κB signaling - Wang, Xiaoxue; Luo, Yilin; Ren, Jie; Xie, Hezhen; Rausch, Marco Aoqi; Rausch-Fan, Xiaohui; Hu, Fei; Zhang, Xueyang (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivePeriodontitis-associated metabolite isoleucine (Ile) plays an important role in periodontitis aggravating colitis. However, how Ile exacerbates colitis is largely unknown.MethodsC57BL/6J mice were used to establish experimental periodontitis and colitis models. Histological alterations of the periodontium and colon were observed by HE staining. The gut barrier function was evaluated by intestinal permeability using FITC-dextran. The expression of tight junctions (ZO-1 and occludin) was detected by immunohistochemical staining or immunofluorescence. The NF-κB signaling pathway was detected using qRT-PCR and Western blot.ResultsExperimental periodontitis and periodontitis-associated metabolite Ile increased the intestinal permeability, downregulated the expression of tight junctions (ZO-1 and occludin), and enhanced the NF-κB signaling pathway of intestinal epithelial cells in dextran sulfate sodium (DSS)–induced colitis mice. Ile downregulated the expression of tight junctions (ZO-1 and occludin) and enhanced the NF-κB signaling pathway in intestinal organoids or IEC-6 cells under inflammatory conditions. IKK-16 (a selective inhibitor of IKKβ that prevents NF-κB activation) rescued excessive inflammatory responses induced by Ile in IEC-6 cells with LPS treatment. In addition, IKK-16 relieved the impairment of intestinal barrier function and inflammatory response induced by Ile in DSS-induced colitis mice.ConclusionOur study unraveled that periodontitis contributed to intestinal barrier function damage and inflammation of intestinal epithelial cells by potentiating NF-κB signaling in the context of colitis and that this was associated with periodontitis-associated metabolite Ile.